Preventing Personal Data Misuse: Legal Protection in Online Loans - Rahayu Hartini; Pramesti, Yashinta Chindy; Moh.Ali, Hasani (Arena Hukum, 2024)
The rapid growth of online lending platforms in Indonesia has raised concerns regarding personal data misuse. This research examines the legal protections available to protect personal data in online lending by emphasising the importance of strict regulations and legal enforcement mechanisms. This research also explores how existing laws, including the Indonesian Personal Data Protection Law, exist. This normative legal research employs a statutory approach. This research highlights gaps in current legislation by analysing cases of personal data breaches and unethical practices. It offers recommendations for strengthening the legal framework to prevent misuse of personal information. The research concludes that a stronger legal approach is needed to protect consumers from potential harm from online lending and promote trust in digital financial services.